MIMESIS, IDEOLOGY, AND THE ROTTEN TEXT: THE CRITIQUE OF REALISM IN ROLAND BARTHES' S/Z - Schubertová, Anna (Bohemica Olomucensia, 2021)
This study examines Roland Barthes' notion critique of realism as it is presented especially in his book S/Z and his essay "The Reality Effect". Barthes criticizes the claim to mimetic representation of "reality" present in realist fiction. As has been pointed out by numerous later theorists, this is a rather reductive view of realism's link to world. The second issue of realism criticized by Barthes is its ideological closedness, juxtaposed in S/Z to his ideal of the writable text but also to Barthes' re-reading of Balzac's novella Sarrasine as fully open and plural. The result of his interpretation, however, does not live up to these claims. Following contemporary theorists of realism, I suggest reading S/Z as a self-legitimizing gesture rather than a serious attempt at understanding realism.
Keywords: Realism; naïve realism; Roland Barthes; mimesis; representation; reality effect; ideology